HUMAN RIGHTS EDUCATION AND THE CURRICULUM OF THE STATE OF SAO PAULO: A DOCUMENTARY ANALYSIS - Sabadini, Marcos Fernandes; Klein, Ana Maria [UNESP] (Fundacao Univ Tocantins, 2020)
Human Rights Education (HRE) is a systematic process that involves developing through historically constructed knowledge, promoting values, attitudes and behaviors committed to democracy and the formation of the subject of rights. The study seeks to identify contents, values and practices converging with an HRE in the Official Curriculum of the State of sao Paulo. It is an applied research that aims to generate knowledge aimed at school pedagogical practice. The problem approach Is qualitative and the techniques used are bibliographic and documentary research. The documents analyzed are: National Human Rights Education Plan, National Human Rights Program 3, PNDH-3, National Human Rights Education Guidelines and Paulista Curriculum. The results demonstrate that some contents, values and practices converging with HRE are present in the curriculum focused on the human area. It is questioned, however, whether there was intentionality in this proposal or whether they coincide with the character and content of the disciplines.
Keywords: Human Rights Education; Curriculum; sao Paulo